Export Versus FDI in Services. (IMF Working Papers; Working Paper ;, 2010)
In the literature on exports and investment, most productive firms are seen to invest abroad. In the Helpman and others (2004) model, costs of transportation play a critical role in the decision about whether to serve foreign customers by exporting, or by producing abroad. We consider the case of tradable services, where the marginal cost of transport is near zero. We argue that in the purchase of services, buyers face uncertainty about product quality, especially when production is located far away. Firm optimisation then leads less productive firms to self-select themselves for FDI. We test this prediction with data from the Indian software industry and find support for it.